Involuntary dislocation home, trauma, resilience, and adversity-activated development - Papadopoulos, Renos K. (London : Routledge, 2021)
Renos K. Papadopoulos clearly and sensitively explores the experiences of people who reluctantly abandon their homes, searching for safer lives elsewhere, and provides a detailed guide to the complex experiences of involuntary dislocation. Involuntary Dislocation: Home, Trauma, Resilience, and Adversity-Activated Development identifies involuntary dislocation as a distinct phenomenon, challenging existing assumptions and established positions, and explores its linguistic, historical, and cultural contexts. Papadopoulos elaborates on key themes including home, identity, nostalgic disorientation, the victim, and trauma, providing an in-depth understanding of each contributing factor whilst emphasising the human experience throughout. The book concludes by articulating an approach to conceptualising and working with people who have experienced adversities engendered by involuntary dislocation, and with a reflection on the language of repair and renewal. Involuntary Dislocation will be a compassionate and comprehensive guide for psychotherapists, clinical psychologists, counsellors, and other professionals working with people who have experienced displacement. It will also be important reading for anyone wishing to understand the psychosocial impact of extreme adversity.
OCLC-licensed vendor bibliographic record.
Keywords: Emigration and immigration -- Psychological aspects; Psychic trauma; PSYCHOLOGY / Psychopathology / Post-Traumatic Stress Disorder (PTSD); PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health